Akibat Hukum Protokol Notaris yang Tidak Diserahkan oleh Ahli Waris kepada Notaris Lain - Brinda Anitha Wirastuti (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2017)
In the notary science known as the "Notary Protocol", is the State Archive which must be kept and maintained by a notary. Once the importance of the storage and security of the notarial protocol, to the notary who has died, there is an obligation of the heir to inform and submit notary protocol to the Regional Supervisory Board (Majelis Pengawas Daerah/MPD), then the Regional Supervisory Board (MPD) designates another notary as the notary receiver of the protocol to receive and store the notary protocol. Notary protocols which are not submitted to other notaries result in harm to the parties, especially if they are a problem and need to be verified in court by the parties or parties concerned. The authority of the Regional Supervisory Board (MPD) is to request a notary protocol to the heirs of a notary who has died.